The Impact Of The Growth In The Number Of Tiktok Users On Digital Marketing Performance And Seller Sales - Axl Reyhan Prasetyo; Albari (Cita konsultindo, 2026)
The rapid increase in the number of TikTok users in Indonesia has brought significant changes in digital marketing patterns and sales activities through the TikTok Shop feature. This study aims to examine the effect of TikTok user growth on digital marketing performance and seller sales by involving the variables of security, customer service quality, perceived value, e-trust, and repurchase intention. This study used a quantitative approach with 175 respondents. Data collection was carried out through the distribution of an online questionnaire compiled using a Likert scale and aimed at TikTok Shop users in Indonesia. The data analysis technique used was Partial Least Square (PLS). The results of the hypothesis testing indicate that customer service quality and perceived value have a significant effect on e-trust. In addition, the variables of security, customer service quality, e-trust, and perceived value were proven to have a significant effect on repurchase intention. However, the results also showed that the security variable did not have a significant effect on e-trust.